2013
DOI: 10.1590/s0100-29452013000100025
|View full text |Cite
|
Sign up to set email alerts
|

An overview on the Brazilian orange juice production chain

Abstract: Brazil is the world's largest producer of oranges and uses more than 70% of the harvested fruits in the production of juices. The amount of processed orange is growing about 10% per year, confirming the trend of the Brazilian citrus for juice production. This research aimed to investigate the Brazilian orange juice production chain from 2005 to 2009. Data from the amount of frozen juice produced and exported, international price of orange juice, and intermediate transactions were assessed in order to make poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
5
0
8
Order By: Relevance
“…Santos et al (2013) reported that the Brazilian orange juice industry went through a period of crisis in the second half of 2007, which was associated to the fall of commodity prices and to the decline in the global demand for the product. This fact can justify the sale price assumed by the model used in the prediction, which was approximately USD 0.20 lower than the last price paid to the producer, according to information available on the CEPEA of March, 2014. According to the United States Department of Agriculture -USDA (2007), agricultural risks are generally organized into five categories: price risk (products and agricultural supplies); production risk; income risk; financial risk; and institutional risk (related to changes in laws or regulations).…”
Section: Resultsmentioning
confidence: 99%
“…Santos et al (2013) reported that the Brazilian orange juice industry went through a period of crisis in the second half of 2007, which was associated to the fall of commodity prices and to the decline in the global demand for the product. This fact can justify the sale price assumed by the model used in the prediction, which was approximately USD 0.20 lower than the last price paid to the producer, according to information available on the CEPEA of March, 2014. According to the United States Department of Agriculture -USDA (2007), agricultural risks are generally organized into five categories: price risk (products and agricultural supplies); production risk; income risk; financial risk; and institutional risk (related to changes in laws or regulations).…”
Section: Resultsmentioning
confidence: 99%
“…No Brasil, anualmente são colhidos aproximadamente 18 milhões de toneladas de laranja, o que torna o país o maior exportador do produto, responsável por 80% da produção mundial de suco de laranja concentrado (Santos et al, 2013).…”
Section: Introductionunclassified
“…Com relação às exportações de frutas processadas, a laranja corresponde a 90% deste total, sendo o Brasil maior fornecedor do mundo. (Santos et al, 2013). Segundo Andrade (2012) a laranja é a principal fruta produzida no Brasil, com 18,1 milhões de toneladas saídas dos pomares em 2010, e responde por 42,9 % do volume total da Fruticultura, um acréscimo na produção em 2,7 % em relação a 2009.…”
Section: Introductionunclassified